Strengthening Students' Spiritual Values Through the Routine of Reading Surat Yasin: A Study on the Implementation of Character Education Based on Islamic Religious Education at SD Negeri 1 Selobanteng - Ainur Rofiq Sofa; Muhammad Hafil Mangkudilaga (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to describe in depth the implementation of the routine of reading Surat Yasin and strengthening the spiritual values of students at SD Negeri 1 Selobanteng. This activity is seen as an important part of character education based on Islamic Religious Education which is carried out regularly every Friday morning. This study uses a qualitative approach with a descriptive type of research. Data was collected through participatory observation, in-depth interviews with PAI teachers, principals, and students in grades I–VI, as well as documentation in the form of photos of activities, school records, and other supporting data. Data analysis is carried out through the process of reduction, data presentation, and inductive conclusion drawn. The results of the study showed that the reading of Surat Yasin was carried out in a structured manner and received full support from the school. This activity not only accustomed students to reading the Qur'an, but also instilled spiritual values such as sincerity, discipline, togetherness, and appreciation for religious values. The process of internalizing values can be seen through changes in students' attitudes and behaviors on a daily basis, especially in the aspects of discipline and respect for teachers. However, there are several obstacles such as time constraints, variations in students' reading abilities, and lack of involvement of a small number of students. Overall, this activity has proven to be effective in supporting the formation of students' religious character through regular habituation and continuous guidance.